Dielectric films for high performance capacitive energy storage: multiscale engineering. Issue 38 (23rd September 2020) - Pan, Hao; Kursumovic, Ahmed; Lin, Yuan-Hua; Nan, Ce-Wen; MacManus-Driscoll, Judith L.
Abstract : This minireview summarizes the very recent advances in energy-storage dielectric films in the framework of engineering at multiple scales. Abstract : Dielectric capacitors are fundamental components in electronic and electrical systems due to their high-rate charging/discharging character and ultrahigh power density. Film dielectrics possess larger breakdown strength and higher energy density than their bulk counterparts, holding great promise for compact and efficient power systems. In this article, we review the very recent advances in dielectric films, in the framework of engineering at multiple scales to improve energy storage performance. Strategies are summarized including atomic-scale defect control, nanoscale domain and grain engineering, as well as mesoscale composite design. Challenges and remaining concerns are also discussed for further performance improvement and practical application of dielectric films.